Bioinformatics analysis of gene expression profile of serous ovarian carcinomas to screen key genes and pathways - Hongjun Fei; Songchang Chen; Chenming Xu (BMC, 2020)
Abstract Background Serous ovarian carcinomas (SCA) are the most common and most aggressive ovarian carcinoma subtype which etiology remains unclear. To investigate the prospective role of mRNAs in the tumorigenesis and progression of SCA, the aberrantly expressed mRNAs were calculated based on the NCBI-GEO RNA-seq data. Results Of 21,755 genes with 89 SCA and SBOT cases from 3 independent laboratories, 59 mRNAs were identified as differentially expressed genes (DEGs) (|log2Fold Change| > 1.585, also |FoldChange| > 3 and adjusted P < 0.05) by DESeq R. There were 26 up-regulated DEGs and 33 down-regulated DEGs screened. The hierarchical clustering analysis, functional analysis and pathway enrichment analysis were performed on all DEGs and found that Polo-like kinase (PLK) signaling events are important. PPI network constructed with different filtration conditions screened out 4 common hub genes (KIF11, CDC20, PBK and TOP2A). Mutual exclusivity or co-occurrence analysis of 4 hub genes identified a tendency towards co-occurrence between KIF11 and CDC20 or TOP2A in SCA (p < 0.05). To analyze further the potential role of KIF11 in SCA, the co-expression profiles of KIF11 in SCA were identified and we found that CDC20 co-expressed with KIF11 also is DEG that we screened out before. To verify our previous results in this paper, we assessed the expression levels of 4 hub DEGs (all up-regulated) and 4 down-regulated DEGs in Oncomine database. And the results were consistent with previous conclusions obtained from GEO series. The survival curves showed that KIF11, CDC20 and TOP2A expression are significantly related to prognosis of SCA patients. Conclusions From all the above results, we speculate that KIF11, CDC20 and TOP2A played an important role in SCA.